Evaluation of Indonesian Tourism Marketing towards Quality Tourism - Dani Fauzi; Panji Arief Sumirat (Master of Management Department, Faculty of Economics, Universitas Bangka Belitung, 2023)
The Ministry of Tourism and Creative Economy of the Republic of Indonesia is dedicated to advancing high-quality and globally competitive tourism endeavors. Beyond mere visitor numbers, the ministry prioritizes quality tourism as its primary objective. This commitment necessitates an effective tourism marketing strategy to foster ideal quality tourism over the next five years (2025-2029). This research evaluates various aspects of tourism marketing strategies, including domestic, international, niche-market, marketing communication, and partnership strategies, aiming to enhance the quality of the tourism industry. Utilizing qualitative methods, specifically document analysis, this study critically examines and gathers evidence from literature, focusing on tourism marketing documents published by the Indonesian Ministry of Tourism and Creative Economy. Findings reveal positive initiatives in Indonesia’s tourism marketing strategy, spanning domestic and international realms, emphasizing niche markets, robust communication strategies, and partnership initiatives, all contributing to the goal of quality tourism. Continuous evaluation is crucial for assessing strategy effectiveness and adapting to evolving market dynamics. Success hinges on accurate planning, sustainable development practices, and vigilant monitoring, underlining the importance of adapting to changing consumer trends and environmental considerations during 2025-2029. Future research should incorporate primary data collection and comparative analyses to integrate sustainable practices for a comprehensive approach to quality tourism.